2019
DOI: 10.1007/s42452-019-1594-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on rotary ultrasonic assisted end grinding of silicon nitride ceramics

Abstract: In this study, rotary ultrasonic assisted end grinding (RUAEG) of silicon nitride (Si 3 N 4) was discussed. In addition, comparison of RUAEG with conventional end grinding was carried out. Machining parameters effect on the process was experimentally and statistically distinguished. Moreover, interaction of the influential parameters was discussed and the optimum condition was obtained. It is concluded from interaction plots that ultrasonic vibration influence on surface roughness was greater in lower cutting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Calculated regression correlations for cutting force based on ultrasonic vibration, tool rotational speed, workpiece rotational speed and feed rate are presented in Table 4. To examine the correlations accuracy, R-squared can be used 29 that is 98.94% for the presented correlations in Table 4.…”
Section: Cutting Forcementioning
confidence: 99%
“…Calculated regression correlations for cutting force based on ultrasonic vibration, tool rotational speed, workpiece rotational speed and feed rate are presented in Table 4. To examine the correlations accuracy, R-squared can be used 29 that is 98.94% for the presented correlations in Table 4.…”
Section: Cutting Forcementioning
confidence: 99%
“…using simulation software, and the simulation model was verified by ultrasonic-assisted milling experiment and the geometric parameters in the machining process were optimized for hole milling. Kai Egashira et al [7][8]. conducted the ultrasonic vibration experiment of hard and brittle materials, and concluded that the causes of edge damage in the process of small hole machining are uneven stress distribution and internal structure.…”
Section: Introductionmentioning
confidence: 99%
“…They have a broad potential for applications in the aerospace, machinery manufacturing, medical, and healthcare fields. However, the development and application of these ceramics are seriously hampered by many problems, such as their low machining efficiency, poor machining quality, and high susceptibility to damage [1][2][3]. Numerous studies have indicated that ultrasonic-assisted milling is one of the most effective machining methods for efficiently processing ceramic materials with limited damage induced to the samples [4][5][6].…”
Section: Introductionmentioning
confidence: 99%